Changes in the leveland structure of the agricultural sector's income in CEE countries as a result of the integration with the European Union - Kita, Katarzyna; Poczta, Walenty; Ziemińska, Anna (Zmiany poziomu i struktury dochodów sektora rolnego w krajach Europy Środkowo-Wschodniej w wyniku integracji z Unią Europejską, 2011)
Financial support for the agricultural sector represents a significant share in the EU budget. The accession of CEE countries into the EU structures gave them the opportunity to benefit from this support. The aim of the paper is to analyze the importance of the subsidies in farm income as well as the changes in the average income levels and its structure in selected countries of Central and Eastern Europe in the pre- and post-accession periods
Ekonomia = Economics, 2011, Nr 2 (14), s. 141-150
Keywords: farm income; subvention; CEE countries